Quality of Life in Endometrial Cancer Survivors: What Does Obesity Have to Do with It? - Amanda Nickles Fader; Heidi E. Frasure; Karen M. Gil; Nathan A. Berger; Vivian E. von Gruenigen (Obstetrics and Gynecology International)
Objective. Most women with type I endometrial cancer (EC) are obese, increasing the risk of morbidity and mortality in this population. The study objective was to evaluate the impact of obesity on quality of life (QOL) and general health status in EC survivors with early-stage disease. Methods. A prospective ancillary analysis of stage I/II EC survivors. The association of BMI with QOL questionnaire variables measured with the functional assessment of cancer therapy (subscales: physical (PWB), functional (FWB), social, and emotional well-being) and the physical (PCS) and mental component summary subscales of the short-form medical outcomes survey was determined. Results. 152 women completed both questionnaires; 81% were obese. After multiple linear regression, BMI was inversely associated with PWB (P=.001), FWB (P=0.048), and PCS (P=.001). Conclusions. Despite the good prognosis associated with early-stage EC, QOL, and physical health are not optimized in obese survivors. This paper highlights the importance of incorporating health-related QOL assessments and obesity interventions during the survivorship period.